Interactive Storytelling - Holloway-Attaway, Lissa,Murray, John T. (Springer Nature Switzerland, 2023)
Virtual Worlds, Performance, Games and Play – As If They Were Here: The Impact of Volumetric Video on Presence in Immersive Augmented Reality Storytelling Traversing Space in The Under Presents (2019), a VR Game – ”It’s About What We Take With Us And What We Leave Behind”: Investigating the Transformative Potential of Pervasive Games with Various Stakeholders – Communal Ritual Play: Repetition and Interpretation of Game Narratives Across Communities – Bridging the gap between the physical and the virtual in tabletop role playing games: exploring immersive VR tabletops – Circulation and Narrative in a Virtual Environment Detecting Player Preference Shifts in an Experience Managed Environment – Applications and Case Studies – ”Bury Me, My Love”: the boundary between reality and fiction in IDNs for smartphone – Traversing boundaries when translating a literary IDN into several languages: a case study – The Ethical Colonizer? Grand Strategy Games, Colonization, and New Ways of Engaging Moral Choices – Gaming the System: Case Study in Investigative Journalism and Playful Interactive Narrative Design to Explain Systemic Bias in Immigration Policy – Fostering Interdisciplinary Learning for Elementary Students through Developing Interactive Digital Stories – Merging site recreation and museum exhibition in archaeology exhibition – Teaching Interactive Digital Narrative Through Found Photography – Late Breaking Works – Figure of speech detection and generation as a service in IDN authoring support – ChatGPT as a Narrative Structure Interpreter – Curatorial Challenges of Exhibiting VR IDN’s in Film Festival Formats – What really happened here? Dealing with uncertainty in The Book of Distance: a critical historiography perspective – A theory-of-mind game for the early detection of frontotemporal dementia – Towards Procedural Generation of Narrative Puzzles for Open World Games – Mind Stories: a Story Making game - From Narrative Therapy to Interactive Narrative Therapy. Empathic Experiences of Visual Conditions with Virtual Reality – The Chronicles of ChatGPT: Generating and Evaluating Visual Novel Narratives on Climate Change Through ChatGPT – A Crossmedia Storytelling Platform to Empower Vulnerable Groups for IT Security – Introducing the Comic Automaton: Interaction Design Options for an Interactive Comic for Higher Education – Comic for Higher Education Dataset Collected Using Illustration Cards – Analyzing Audience Comments: Improving Interactive Narrative with ChatGPT – Integrating Storytelling and Making: A Case Study in Elementary School – Designing a Language Model-Based Authoring Tool Prototype for Interactive Storytelling – Alice Dali MR: A Mixed Reality Interactive Narrative Experience – Exploring the Union Between Procedural Narrative and Procedural Content Generation – A Design-Oriented Framework for Interactive Digital Narrative in Virtual Reality - Focus on Branching Narrative and Agency – What Is Waiting for Us at the End? Inherent Biases of Game Story Endings in Large Language Models – Breaking Bad: Unraveling Influences and Risks of User Inputs to ChatGPT for Game Story Generation – Playing Story Creation Games With Large Language Models: Experiments With GPT-3.5 – Traversing language, the author, and the word in Amira Hanafi’s A Dictionary of the Revolution. This two-volume set LNCS 14383 and LNCS 14384 constitutes the refereed proceedings of the 16th International Conference on Interactive Digital Storytelling, ICIDS 2023, held in Kobe, Japan, during November 11–15, 2023. The 30 full papers presented in this book together with 11 short papers were carefully reviewed and selected from 101 submissions. Additionally, the proceedings includes 22 Late Breaking Works. The papers focus on topics such as: theory, history and foundations; social and cultural contexts; tools and systems; interactive narrative design; virtual worlds, performance, games and play; applications and case studies; and late breaking works.
10.1007/978-3-031-47658-7
Keywords: Computers.; Computer engineering.; Computer networks .; Artificial intelligence.; Digital humanities.